Chorus-Line Algorithm for Clock Synchronization - Ailane Mohamed Toufik; Jianguo Yao; Yuan Jin (IEEE Access, 2018)
Today's modern technology relies increasingly on real-time distributed systems. Such systems could gain a remarkable amount of both academic and industrial attention in several fields. Real-time synchronization of the distributed sub-systems is one key success that raises many challenges. In this paper, we first discuss the existing time-triggered protocol known as TTEthernet. Furthermore, an analytical study made on flying dunlin birds is used here to adopt the same mechanism to optimize the synchronization process. The natural phenomenon consists of avian flocks performing manoeuvres with high accuracy in a small window of time. Inspired by this phenomenon, a real-time synchronization algorithm is proposed. Results reflect the reliability of the new algorithm and provide a remarkable percentage of optimization compared with other leading protocols.